Natural history of dilated cardiomyopathy : clinical, echocardiographic and laboratory profile of patients with dilated cardiomyopathy - Dziewięcka, Ewa Maria (2022)
The study was conducted in the retrospective and prospective cohorts of patients with dilated cardiomyopathy (DCM). As part of a retrospective study, the usefulness of the most used prognostic scales dedicated to heart failure was analysed in DCM. Then, due to their inaccuracy, a dedicated DCM model was developed - Krakow DCM Risk Score. This model turned out to be more effective than the existing scales, and its external validation showed high prognostic efficiency (accuracy of 70-77%). The model also successfully identified patients at high risk of death (HR 3.4; 95% CI 1.9-6.1). In addition, the retrospective analysis showed a high frequency of increased risk of pulmonary hypertension (PH) in DCM (53%), which turned out to significantly increase the risk of death (HR 1.8; 95% CI 1.1-3.0). In the prospective analysis, left ventricular reverse remodeling (LVRR) was found in 52% of DCM patients. A significant association of tissue microRNA-133a with the presence of LVRR has been demonstrated. In addition, significant differences were observed in the sphericity index (SI - assessing the degree of sphericity of the left ventricle) during the LVRR and the progressive remodeling of the left ventricle (in patients without LVRR). In conclusion, the created Krakow DCM Risk Score turned out to have a high prognostic value in DCM with good discrimination of patients with a high risk o
Keywords: dilated cardiomyopathy; mortality; prognostic stratification; left ventricle reverse remodeling; pulmonary hypertension